Biological Activities of Aurones: A Brief Summary - Zhu, Qiang; Zheng, Xing; Tan, Yan; Luo, Zhongqin; Yao, Xu; Chen, Hongfei (Mini-Reviews in Organic Chemistry, 2025)
Aurones are structural isomers of flavones and flavonols with the basic C6–C3–C6 skeleton arranged as (Z)-2-benzylidenebenzofuran-3(2H)-one, which contain an exocyclic carbon-carbon double bond bridging the benzofuranone and phenyl rings. In aurone, a chalcone-like group is closed into a 5-membered ring instead of the 6-membered ring more typical of flavonoids, which forms the core for a family of derivatives that are known collectively as aurones. As a kind of flavonoids, aurones are widely distributed in many plants which provide yellow color to some popular ornamental flowers. For a long time aurones had not got enough attention, while in recent years, finally this chemical is coming into researchers' view. As the secondary metabolite in the family of flavonoids, aurones displayed various biological activities, including antioxidant, antiparasitic, antitumor, antiviral, antibacterial, anti-inflammatory, anti-SARS-CoV-2 and neuropharmacological activities. Therefore, aurones have attracted the attention of more and more chemists and pharmaceutical chemists, who realized that it is possible to get lead compounds with better activities via structural modifications of aurones. In some research works, aurone and its derivatives have exhibited good activity, e.g., Xie discovered the heterocyclic variant of the (Z)-2-benzylidene-6-hydroxybenzofuran-3(2H)-one scaffold that possessed low nanomolar in vitro potency in cell proliferation assays using various cancer cell lines, in vivo potency in prostate cancer PC-3 xenograft and zebrafish models, and absence of appreciable toxicity, which proved that aurones are valuable compounds worthy of further study. Herein, the biological activities of aurone derivatives are reviewed, which covers the literature since 2000, in which the strategies to develop bioactive aurone derivatives and the structure-activity relationship are highlighted.
Keywords: biological activities